Faster speed of onset of the depressive episode is associated with lower cytokine serum levels (IL-2, -4, -6, -10, TNF-α and IFN-γ) in patients with major depression. (September 2021) - Buspavanich, Pichit; Adli, Mazda; Himmerich, Hubertus; Berger, Maximilian; Busche, Marlene; Schlattmann, Peter; Bopp, Sandra; Bschor, Tom; Richter, Christoph; Steinacher, Bruno; Stoppel, Christian; Hindinger, Claudia; et al.
Abstract: Introduction: Cytokines might play a key role in the pathophysiology of major depressive disorder (MDD). The speed of onset of depressive episodes has been discussed as an important clinical parameter in MDD. The aim of this study was to investigate a potential influence of the speed of onset of the depressive episode on cytokine serum levels. Method: Serum level of the cytokines interleukin (IL)-2, IL-4, IL-6, IL-8, IL-10, tumor necrosis factor alpha (TNF-α), interferon-gamma (IFN-γ) granulocyte and monocyte colony stimulating factor (GM-CSF) were measured in a total of 92 patients with MDD that did not respond to at least one previous antidepressant treatment. Patients were retrospectively divided in two groups: Faster (≤4 weeks) and slower (>4 weeks) onset of the depressive episode defined as the time passing from the first depressive symptoms to a full-blown depressive episode by using information from a clinical interview. Results: We found significantly lower serum levels of IL-2, IL-4, IL-6, IL-10, TNF-α and IFN-γ in patients with a faster onset compared to patients with a slower onset of the depressive episodes. Furthermore, lower cytokine serum levels of IL-2, IL-8, IL-10 and IFN-γ were found in patients with a shorter duration (less than 6 months) compared to a longer duration (6–24 months) of the current depressive episode. This effect on cytokines was independent from the effect of the speed of onset of the depressive episode. Conclusions: Patients with faster onset of the depressive episode might represent a biological subtype of MDD with lower serum levels of IL-2, IL-4, IL-6, IL-10, TNF-α and IFN-γ. Highlights: Cytokines might play a key role in the pathophysiology of depression. Serum level of cytokines were measured in 92 patients with MDD. Faster onset of the depressive episode was associated with lower serum levels for IL-2, -4, -6, -10, TNF-α and IFN-γ. Depressive episodes with a faster onset might represent a biological subtype of depression.